Las Las competencias teológicas del estudiante javeriano: una aproximación a la cuestión - Martínez Ruíz, Víctor (2023)
The Theology area in Humanities Department, frames the training that gives to its students in the typical skills approach of current educational standardized trends in a global world. In this sense, it is imperative to reflect on the needs of theological education and the construction of an alternative approach on skills, not only for the specific area but also to assert their own discourse over the homogenizing that circulate about this matter.